Tinjauan Persepsi Mahasiswa Pendidikan IPA Terhadap Kemampuan Berpikir Kritis Dalam Pembelajaran - Putri, Dwi Charisma; Sri Wahyuni; Astuti, Sri Rejeki Dwi; Barid, Siti Shofa Assyifa’Ul Qulbi (Universitas Tidar, 2026)
This study was conducted to describe science education students' perceptions of critical thinking skills, particularly in terms of critical openness and reflective skepticism. A quantitative approach using descriptive methods was applied to 52 fifth-semester students selected through convenience sampling. Data were collected using the Critical Thinking Disposition Scale (CTDS) questionnaire and analyzed descriptively through the calculation of average scores and percentages. The results showed that students' critical thinking skills were in the moderate category with a total score of 50%. Reflective skepticism scored higher (51%) than critical openness (49%), indicating that students were stronger in assessing and reflecting on information than in accepting new perspectives. These findings emphasize the need for more dialogical and reflective learning strategies so that both aspects of critical thinking develop in a balanced manner. In addition, this study contributes to the development of critical thinking skills in higher education and opens up opportunities for further study related to other factors that influence student perceptions.